2020
DOI: 10.1029/2020gl087403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tracing of Riverine Soil Organic Matter From the Central Himalaya

Abstract: The isomer distribution of branched glycerol dialkyl glycerol tetraethers (brGDGTs) in soils has been shown to correlate to the local mean annual temperature. Here, we explore the use of brGDGT distributions as proxy for the elevation at which soil organic carbon is preferentially mobilized in the Central Himalaya. Soil brGDGT distributions collected along an altitudinal profile, spanning elevations from 200 to 4,450 m asl, are linearly correlated to elevation. We use this calibration to trace the provenance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…In contrast to in the dry season, brGDGT distributions do not change in the wet season, when the river plume extends beyond the Godavari mouth and the water is less saline (<3 psu) (Sridhar et al, 2008;Kirkels et al, 2020b). The seasonal difference in salinity indicates once more that the soil signal is only effectively exported to the Bay of Bengal in the wet season, and supports previous studies that have shown that substantial soil mobilisation is needed (e.g., by a distinct season with increased precipitation) to export soil-derived brGDGTs downstream (Guo et al, 2020;Kirkels et al, 2020a;Märki et al, 2020).…”
Section: Godavari Deltasupporting
confidence: 80%
See 2 more Smart Citations
“…In contrast to in the dry season, brGDGT distributions do not change in the wet season, when the river plume extends beyond the Godavari mouth and the water is less saline (<3 psu) (Sridhar et al, 2008;Kirkels et al, 2020b). The seasonal difference in salinity indicates once more that the soil signal is only effectively exported to the Bay of Bengal in the wet season, and supports previous studies that have shown that substantial soil mobilisation is needed (e.g., by a distinct season with increased precipitation) to export soil-derived brGDGTs downstream (Guo et al, 2020;Kirkels et al, 2020a;Märki et al, 2020).…”
Section: Godavari Deltasupporting
confidence: 80%
“…Although lipid biomarkers represent only a small part of the total OC, their source-or environmental-specific signature renders them as promising tracers in river systems (e.g., Eglinton et al, 2021). Over the past decade, bacterial membrane lipids, so-called branched glycerol dialkyl glycerol tetraethers (brGDGTs), have been used to trace soil organic matter inputs into rivers and continental margins (e.g., Hopmans et al, 2004;Weijers et al, 2009a;Kim et al, 2012;Zell et al, 2013a,b;Kirkels et al, 2020a;Märki et al, 2020). BrGDGTs occur globally in soils and peats, and can vary in the number (4-6) and position of methyl branches (5/5' or 6/6', defined as 5-methyl and 6-methyl) attached to linear C28 alkyl chains, as well as the presence of 0-2 cyclopentane moieties (Weijers et al, 2007a;De Jonge et al, 2013; see figures therein for the molecular structures).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples are further described in ref. 52 . The samples integrate the surface soil layer of a depth of up to 15 cm.…”
Section: Samplingmentioning
confidence: 99%
“…The stoichiometric ratios and stable isotopic compositions of C (carbon) and N (nitrogen) in organic matter were developed as effective methods to trace the organic matter sources and identify predominant processes [7,8]. Moreover, the sediment profiles of stoichiometric ratios and stable isotopes of organic matter can reflect the historical changes in aquatic ecosystem productivity and terrigenous organic matter transportation processes, providing important information for the interpretation of paleoenvironmental conditions [4,5,9,10].…”
Section: Introductionmentioning
confidence: 99%